Moving Towards the Reliability-oriented Design of Hairpin Winding for EV Traction Machines Driven by SiC Inverter - Xiaowei Ju; Yue Zhang; Zhiwei Xue; Yuan Cheng; Shumei Cui (CES Transactions on Electrical Machines and Systems)
With the development of high-frequency and high-voltage traction machines (TM) incorporating hairpin windings (HW) and SiC inverters for electric vehicles (EV), both the interturn voltage stress and temperature within HW are rising, increasing the risk of partial discharge (PD), and presenting significant challenges to insulation safety. Therefore, this paper addresses this issue and proposes potential solutions. Firstly, the paper examines an 8-pole, 48-slot, 6-layer HW TM to highlight the unique characteristics of this winding structure, and explains the uneven distribution of interturn voltage stress and temperature. Subsequently, a high-frequency equivalent circuit model of the HW TM prototype is developed. The error of simulation and experiment is only 5.7 %, which proves the accuracy of the model. Then, an improved HW scheme is proposed to lower the maximum voltage stress by 29.3 %. Furthermore, the temperature distribution of HW TM is analyzed to facilitate a detailed examination of the impact of temperature on insulation PD. Finally, the partial discharge inception voltage (PDIV) of interturn insulation, considering temperature effects, is calculated and verified through experiment. The paper proposes a reliability-oriented design method and process for HW TM. It demonstrates that the reliability-oriented design can achieve PD-free performance in the design stage of HW.